Cost-effectiveness in an interprofessional training ward within a university department for internal medicine: a monocentric open-label controlled study of the A-STAR Regensburg - Sophie Schlosser-Hupf; Elisabeth Aichner; Marcus Meier; Sheila Albaladejo-Fuertes; Anna Mahnke; Kirstin Ruttmann; Sophia Rusch; Bernhard Michels; Alexander Mehrl; Claudia Kunst; Stephan Schmid; Martina Müller (Frontiers Media S.A., 2024)
IntroductionInterprofessional collaboration in healthcare involves diverse professionals working together to address complex patient needs. Interprofessional training wards offer workplace-based interprofessional education in real healthcare settings, fostering collaborative learning among students. While their educational value is widely recognized, debates persist regarding their cost-effectiveness due to limited research. This study assesses the cost efficiency of the interprofessional training ward Regensburg (A-STAR) within the Department of Internal Medicine I at the University Hospital Regensburg, compared to conventional wards.MethodsFrom October 2019 to December 2022, 7,244 patient cases were assigned to A-STAR or conventional wards by case managers, with a comprehensive analysis of all associated revenues and costs.ResultsA-STAR treated 1,482 patients, whereas conventional wards treated 5,752 patients, with more males and younger patients at A-STAR. A-STAR achieved higher profit per case (€1,508.74) attributed to increased revenues and reduced material costs. It generated an average of €1,366.54 more Diagnosis Related Groups (DRG) revenue per case annually than conventional wards, due to greater medical complexity reflected in a higher case-mix index (CMI: 2.4 vs. 2.2). The increased case complexity led to longer patient stays (9.0 vs. 8.1 days) and fewer cases treated annually at A-STAR (27.4 cases/year vs. 37.8 cases/year). The higher CMI did not result in a higher proportion of patients requiring isolation. A-STAR exhibited a higher capacity utilization rate (87.1% vs. 83.9%). Personnel costs per case at A-STAR were initially elevated due to enhanced observation by the senior physician but were gradually mitigated by expanding A-STAR's bed capacity. Material costs were consistently lower on a per-case basis at A-STAR (€1512.02 vs. €1577.12), particularly in terms of medication expenses, indicating more resource-efficient operations. From the A-STAR graduates, 18 individuals were recruited for permanent positions as doctors or nurses over 2 years.ConclusionA-STAR demonstrates economic efficiency and stability even during the COVID-19 pandemic. The substantial personnel acquisition is likely influenced by high levels of satisfaction with education and work and is economically relevant in medical staff shortages. These findings provide a compelling rationale for the broader implementation of interprofessional training wards, establishing them as vital platforms for nurturing future professionals.